THE MODEL THEORY APPROACH "CARE, CORE, CURU” FOR PATIENTS WITH CARDIOVASCULAR DISEASES - Annisaa Fitrah Umara (International Journal of Nursing and Health Services (IJNHS), 2018)
The impact of cardiovascular disease was felt by individuals and global. By individual approach, prevention and supervision are needed to reduce the burden. Nurses have an essential role in giving holistic standards of nursing practice. The purpose of this study is to provide an overview of the case management of patients with cardiovascular disease by using the theoretical approach "care, core, and cure" model theory. The method used is a case study of 30 patients with Cardiovascular Diseases in Harapan Kita Jakarta National Heart Center. Inform consent was obtained, the initial name and code were assigned to all participant. The results are nine acute coronary syndrome patient, four heart failure patient, ten heart surgery patient, and seven arrhythmia patient. The majority of patients were male, an average age more than 41 years old. Most risk factors are caused by hypertension and smoking. In the acute phase, the "care" and "cure" aspects were more prominent than the "core" aspect. In the non-acute phase, patients need rehabilitation and health education, so the more prominent aspects are "care" and "core" than "cure." The aspect "care" provides an overview of risk factors that result in cardiovascular disease. The "core" aspect shows the needed of education and the "cure" aspects indicating the necessity for medical therapy in patients with cardiovascular disease. In the "Care" aspect, independence nursing intervention can be identified and easily evaluated. In the “Core” aspect, the nurse can recognize the patient's needs during the treatment and provided nursing care plans as needed. In the “Cure” aspect, can be increased coordination among health care providers. Nurse need to develop the model of nursing theory approach in providing nursing care for patients with Cardiovascular Diseases, especially patients who have the opportunity to undergo rehabilitation.